Distant obscured quasars - Martínez-Sansigre, A; Martinez-Sansigre, Alejo (2006)
﻿ This thesis presents a study of high-redshift obscured (type-2) quasars, selected at mid-infrared and radio wavelengths. This population had remained elusive, even to hard X-ray surveys, and in Chapter 2 I compare the selection of type-2 quasars in X-ray and mid-infrared surveys, as well as explaining the criteria I will use to search for these objects at z ~ 2, around the peak in the unobscured (type-1) quasar activity. Chapter 3, presents a sample of radio-intermediate type-2 quasars selected from the criteria de- scribed in Chapter 2. Optical spectroscopy shows indeed that at least half of the objects have the characteristic narrow emission lines, and lie around the expected redshift of z = 2. The other half of the objects are consistent with also being type-2 quasars at similar redshifts, although no emission lines are visible. In Chapter 4,1 discuss the possibility of two types of obscured quasars, some obscured by a dusty torus and some by a dusty host galaxy, to explain the lack of emission lines in half of the sample. I model the number of type-1 quasars expected to follow similar selection criteria and at the same redshifts as our type-2 quasars, and find that the obscured quasars outnumber the unobscured by a ~2-3:1 ratio. I conclude that most supermassive black hole growth is obscured by dust. When comparing this to predictions from unified schemes, I find that this result is only consistent with the schemes provided host-obscuration is indeed happening. The lower ratio of type-2 to type-1 quasars inferred from X-ray surveys (~1:1) suggests that some of the type-2 quasars in this sample might be Compton thick. Radio data taken at three frequencies, are presented in Chapter 5, to study the spectral properties and intrinsic luminosities of our sample. I show that some type-2 quasars have flat radio spectra, which is inconsistent with obscuration by the torus, but consistent with host-obscuration. Some gigahertz-peaked spectra, characteristic of young radio jets, are present, but the majority of the sources have very steep spectra. These steep spectral indices can be explained by active developed jets in which continuous injection of electrons is accompanied by inverse-Compton losses against the cosmic microwave background. In Chapter 6, I select a similar sample of type-2 quasars in a different field, where X-ray data are available. The selection criteria are kept identical, except for the radio flux density cut, which is lowered. This is expected to introduce significant numbers of starburst contaminants. To filter these out, and due to a lack of spectroscopy, I use a bayesian method to fit the spectral energy distributions, obtain photometric redshifts, and select between a quasar and a starburst model. I measure the X-ray properties for the resultant sample of type-2 quasars. The entire sample is found to be Compton-thick, and repeating the modelling of Chapter 4, I find that the population of Compton-thick quasars is at least comparable to the population of unobscured quasars, and probably larger.